Increasing insecticide resistance in Anopheles funestus and Anopheles arabiensis in Malawi, 2011–2015. (December 2016) - Mzilahowa, Themba; Chiumia, Martin; Mbewe, Rex; Uzalili, Veronica; Luka-Banda, Madalitso; Kutengule, Anna; Mathanga, Don; Ali, Doreen; Chiphwanya, John; Zoya, John; Mulenga, Shadreck; Dodoli, Wilfred; et al.
Abstract Background Susceptibility of principalAnopheles malaria vectors to common insecticides was monitored over a 5-year period across Malawi to inform and guide the national malaria control programme. Methods Adult blood-fedAnopheles spp. and larvae were collected from multiple sites in sixteen districts across the country between 2011 and 2015. First generation (F1 ) progeny aged 2–5 days old were tested for susceptibility, using standard WHO procedures, against pyrethroids (permethrin and deltamethrin), carbamates (bendiocarb and propoxur), organophosphates (malathion and pirimiphos-methyl) and an organochlorine (DDT). Results Mortality ofAnopheles funestus to deltamethrin, permethrin, bendiocarb and propoxur declined significantly over the 5-year (2011–2015) monitoring period. There was wide variation in susceptibility to DDT but it was not associated with time. In contrast, An. funestus exhibited 100% mortality to the organophosphates (malathion and pirimiphos-methyl) at all sites tested. There was reduced mortality ofAnopheles arabiensis to deltamethrin over time though this was not statistically significant. However, mortality ofAn. arabiensis exposed to permethrin declined significantly over time.Anopheles arabiensis exposed to DDT were more likely to be killed if there was high ITN coverage in the mosquito collection area the previous year. There were no other associations between mosquito mortality in a bioassay and ITN coverage or IRS implementation. Mortality ofAn. funestus from four sites exposed to deltamethrin alone ranged from 2 to 31% and from 41 to 94% when pre-exposed to the synergist piperonyl butoxide followed by deltamethrin. For permethrin alone, mortality ranged from 2 to 13% while mortality ranged from 63 to 100% when pre-exposed to PBO. Conclusion Pyrethroid resistance was detected inAn. funestus andAn. arabiensis populations across Malawi and has worsened over the last 5 years. New insecticides and control strategies are urgently needed to reduce the burden of malaria in Malawi.